2022
DOI: 10.1371/journal.pbio.3001456
|View full text |Cite
|
Sign up to set email alerts
|

Glial immune-related pathways mediate effects of closed head traumatic brain injury on behavior and lethality in Drosophila

Abstract: In traumatic brain injury (TBI), the initial injury phase is followed by a secondary phase that contributes to neurodegeneration, yet the mechanisms leading to neuropathology in vivo remain to be elucidated. To address this question, we developed a Drosophila head-specific model for TBI termed Drosophila Closed Head Injury (dCHI), where well-controlled, nonpenetrating strikes are delivered to the head of unanesthetized flies. This assay recapitulates many TBI phenotypes, including increased mortality, impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 147 publications
0
30
0
Order By: Relevance
“…AMPs are important for regulation of normal functions of the insect brain, e.g., sleep and non-associative learning in Drosophila [ 25 , 26 ]. Results reported by Dissel et al showed that the transcript levels of metchnikowin ( Mtk ), drosocin ( Dro ), and attacin ( Att ) were differentially increased in glia, neurons, and the head fat body, respectively, in sleep-deprived flies.…”
Section: Amps In the Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPs are important for regulation of normal functions of the insect brain, e.g., sleep and non-associative learning in Drosophila [ 25 , 26 ]. Results reported by Dissel et al showed that the transcript levels of metchnikowin ( Mtk ), drosocin ( Dro ), and attacin ( Att ) were differentially increased in glia, neurons, and the head fat body, respectively, in sleep-deprived flies.…”
Section: Amps In the Nervous Systemmentioning
confidence: 99%
“…In contrast, loss of Def extended survival, indicating that the Drosophila immune response to TBI, including the induction of AMP expression, may result in different effects. Moreover, in this research, a link between the immune response and sleep in flies was demonstrated, as loss of Relish protected against impaired control of sleep and movement after TBI [ 26 ].…”
Section: Amps In the Nervous Systemmentioning
confidence: 99%
“…While Drosophila AMPs were initially investigated for their contribution to host defence, AMP upregulation is also observed in non-immune contexts, including anti-tumor defence [26][27][28], neurodegeneration [29][30][31][32][33], and aging [34,35]. This suggests that AMPs could have roles beyond their traditional function as microbicidal agents.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 25, 2022. ; https://doi.org/10.1101/2022.08. 24.504952 doi: bioRxiv preprint tumor defence [26][27][28], neurodegeneration [29][30][31][32][33], and aging [34,35]. This suggests that AMPs could have roles beyond their traditional function as microbicidal agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation